2017
DOI: 10.1016/j.healun.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in iron homeostasis result in accelerated rejection after experimental heart transplantation

Abstract: We provide novel insights into the understanding of disturbances in iron homeostasis and their consequences after HTX, allowing novel insights regarding improvements in personalized immunosuppression to prolong allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Direct comparison of our results with previous reports appears difficult, as we transplanted donor hearts cervically 21,22 and not heterotopically 17,19. Whereas others applied multiple dosages of CTLA4-Ig resulting in survival times of 30 or 60 days for cardiac grafts,17,19 we administered only 1 single application of CTLA-4 Ig at d2 posttransplantation, which led to a mean survival of 50 days 22.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Direct comparison of our results with previous reports appears difficult, as we transplanted donor hearts cervically 21,22 and not heterotopically 17,19. Whereas others applied multiple dosages of CTLA4-Ig resulting in survival times of 30 or 60 days for cardiac grafts,17,19 we administered only 1 single application of CTLA-4 Ig at d2 posttransplantation, which led to a mean survival of 50 days 22.…”
Section: Discussionmentioning
confidence: 75%
“…It has been demonstrated that the neutralization of NKG2D in combination with co-stimulation blockade results in prolonged cardiac graft survival 17,19. We therefore transplanted BALB/c-derived hearts into either C57BL/6 or Klrk1 -/- mice receiving a single dose of abatacept at d2 posttransplantation 22. Surprisingly, whereas co-stimulation blockade resulted in a median survival of 50 days in wildtype animals, Klrk1 -/- mice treated with abatacept displayed significantly reduced graft survival (median survival: 27 days; P = .0015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line, the administration of iron isomaltoside had consistent yet not significant effects on effector/ memory tumor infiltrating lymphocyte populations. In contrast, numbers of FoxP3 + CD4 + Tregs were comparable across treatment arms suggesting that the adverse effects of iron towards effector T cell populations where direct rather than indirect and Treg-mediated (72,73).…”
Section: Discussionmentioning
confidence: 92%
“…This is particularly concerning because of the interaction of iron with allo‐immune response and in view of emerging evidence that suggests a potential role for iron in the ischaemia–reperfusion injury of the graft. The evidence even suggests that disturbance in iron homeostasis could affect graft survival and risk of rejection after heart transplantation …”
Section: Is Intravenous Iron Supplementation In Patients With Hfref Amentioning
confidence: 99%